Acordo de leniência na Lei de Improbidade Administrativa e na Lei Anticorrupção - Santos, Kleber Bispo dos (2017)
The leniency agreement stated by Brazilian Law no. 12.846/2013, also known as Anticorruption Act, is an extremely useful tool in preventing corruption because it provides for severe administrative sanctions to legal entities involved in practices that harm both domestic and foreign Public Administration, particularly in major agreements involving public works, infrastructure and the rendering of public services. However, before enactment of the Anticorruption Act, the Misconduct in Office Act, in Article 3, already provided for the liability of legal entities that induce, cooperate or benefit from misconduct practices, which are defined by law as being similar, and sometimes equal to the harmful practices outlined by the Anticorruption Law. In such a scenario, where two systems defining liability for legal entities coexist, and in view of the uncertainties and legal insecurity surrounding the adoption of leniency agreements, which is why this institute is scarcely used, and which in our view represents a drawback for society, we endeavor to present a reading and an interpretation of so valuable an institute by applying the principles enshrined in the Federal Constitution and by approaching issues such as the relevant requirements, the possibility to refuse a proposal, the agents endowed with competence to enter into leniency agreements, the effects thereof on other spheres or systems defining liability, with specific focus on the system under the Misconduct in Office Act, and also on the possibility that leniency agreements be made by legal entities under the system defining liability provided for the Misconduct in Office Act– Law no. 8429/92